2009
DOI: 10.1016/j.molstruc.2009.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Conformational stability of allyl alcohol from temperature dependent infrared spectra of rare gas solutions, ab initio calculations, r0 structural parameters, and vibrational assignment

Abstract: a b s t r a c tVariable temperature (À55 to À145°C) studies of the infrared spectra (4000-50 cm À1 ) of allyl alcohol (3-hydroxypropene), CH 2 @CHCH 2 OH, dissolved in liquid krypton and/or liquid xenon have been carried out. The infrared spectra of the gas and solid have also been recorded. From these data four of the five possible stable conformers have been identified and their relative stabilities determined. The order of the conformers stabilities has been obtained experimentally where the first indicator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 32 publications
(52 reference statements)
0
20
0
Order By: Relevance
“…Recently, we have been investigating the conformation stability and determined the structural parameters of several organoamines and alcohols . One of the first amines studies was ethylamine, which was determined to have the trans conformer more stable by 54 ± 4 cm –1 (0.65 ± 0.05 kJ/mol) than the gauche form.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have been investigating the conformation stability and determined the structural parameters of several organoamines and alcohols . One of the first amines studies was ethylamine, which was determined to have the trans conformer more stable by 54 ± 4 cm –1 (0.65 ± 0.05 kJ/mol) than the gauche form.…”
Section: Introductionmentioning
confidence: 99%
“…Recent high‐level ab initio calculations establish that the most stable of the five possible conformers of allyl alcohol (2‐propen‐1‐ol), 1a , are the + ac,−sc and sp , +sc where the OH hydrogen is in the vicinity of the double bond. These are followed by the sp , ap , + ac , ap and + ac , +sc conformers, in that order . Again, for 2‐methylpropen‐1‐ol, according to ab initio calculations the + ac , −sc and sp , +sc conformers are the most stable .…”
Section: Discussionmentioning
confidence: 92%
“…A recent review drew attention to the importance of unconventional, weak hydrogen bonds, CH/ n , CH/π and XH/π (X = O, S, Se), in determining the conformations of organic compounds and bioconjugates . Early infrared (IR) spectroscopic studies of small unsaturated alcohols are confirmed by work which in many cases combines IR and/or microwave (MW) spectroscopy, and gas electron diffraction (GED) measurements and photoelectron spectroscopy, with ab initio calculations, to identify the preferred conformers. These studies of the conformational equilibria show them to be dominated by OH/π interactions, and the proximity of putative donors and acceptors is frequently taken as demonstrating that intramolecular hydrogen bonding (IHB) occurs.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that the energies of the three lowest conformers above the g'GG't minimum differ by up to 1 kJ mol −1 means that the most important conformer populations, based on the relative Gibbs energies at 298 K, are significantly different from the published values. Variations in the MP2 values for allyl alcohol, for example, with different basis sets suggest that this is not necessarily due to the use of the more economical method 68. The leveling effect of solvation is much less marked than in the case of 1‐Me , except for some relatively high‐energy conformers, notably V, VII, VIII, and X.…”
Section: Resultsmentioning
confidence: 99%